Circular Economy Practices and Material Flow Cost Accounting: Toward Sustainable Development Through Green Intellectual Capital - Fadjrihana, Meidah; Mulyasari, Windu (International Journal of Economic Research and Financial Accounting, 2025)
This research explores how manufacturing companies listed on the Indonesia Stock Exchange based on the Jakarta Stock Exchange Industry Classification (JASICA) from 2020 to 2023 can implement circular economy practices and material flow cost accounting in their activities, which not only prioritize profit but also care about environmental impact and achieve sustainable development with green intellectual capital as mediation. Referring to the resource-based view theory and the triple bottom line. Using a quantitative method with purposive sampling technique involving 109 manufacturing industry companies with 436 observations over 4 years. The findings of this study used STATA 14 and selected the random effects model (REM), which resulted in circular economy practices and green intellectual capital impacting sustainable development. However, circular economy practices do not impact green intellectual capital. Material flow cost accounting also does not impact sustainable development or green intellectual capital, and green intellectual capital cannot mediate the relationship between circular economy practices and material flow cost accounting. However, circular economy practices and material flow cost accounting have a significant simultaneous impact on sustainable development. The implication of this research is the need for companies to efficiently and comprehensively implement these practices simultaneously in achieving sustainable development. It is hoped that this research can make a fair contribution to sustainable development efforts in the manufacturing industry and other industries